The influence of physical exercise as a component of cardiac rehabilitation on endothelial dysfunction – review of the related research - Domka-Jopek, Elżbieta; Lenart-Domka, Ewa (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
Endothelial dysfunction means any disturbance in the vascular endothelial function. There are many data indicating that endothelial dysfunction is a source of numerous vascular diseases. Cardiac rehabilitation, especially connected with increasing physical activity, plays an important role in the prophylaxis of vascular diseases complications in patients. Physical activity causes favorable changes in the circulatory system and improves psychophysical status. It is the base of healthy life style and fundamental element of primary and secondary prevention of cardiovascular diseases. Cardiac rehabilitation after acute coronary incidents reduces total mortality and decreases the risk of next cardiac intervention. Similar beneficial effects may be observed in chronic heart failure. Some reports attempt to explain mechanisms responsible for favorable effect of rehabilitation in primary and secondary prevention of cardiovascular disease. Many authors suggest, that cardiac training improves disturbed function of endothelium in cardiac diseases (hypertension, ischemic heart disease, chronic heart failure). Improved prognosis in patients with cardiovascular diseases after cardiac rehabilitation seems to be dependent on improvement in endothelial function.

Dysfunkcja śródbłonka oznacza ubytek jakiejkolwiek z jego funkcji. Istnieje wiele danych upatrujących źródła chorób sercowo-naczyniowych w upośledzonej funkcji śródbłonka. Wśród działań mających na celu zapobieganie następstwom chorób układu krążenia istotną rolę przypisuje się rehabilitacji kardiologicznej, a zwłaszcza zwiększeniu aktywności fizycznej pacjentów. Aktywność fizyczna, wywołując korzystne zmiany fizjologiczne w czynności układu krążenia, redukując czynniki ryzyka chorób serca, poprawiając stan psychofizyczny pacjentów stała się podstawą zdrowego stylu życia oraz fundamentalnym elementem prewencji pierwotnej i wtórnej chorób układu krążenia. Zastosowanie rehabilitacji kardiologicznej u chorych po przebyciu ostrych incydentów wieńcowych redukuje śmiertelność całkowitą oraz zmniejsza ryzyko kolejnych interwencji kardiologicznych. Podobnie korzystne efekty widoczne są w przewlekłej niewydolności serca. W ostatnich latach pojawiło się szereg doniesień próbujących wytłumaczyć mechanizmy odpowiedzialne za pozytywny efekt rehabilitacji pacjentów z chorobami sercowo-naczyniowymi. Wielu autorów potwierdza, że kompleksowa rehabilitacja kardiologiczna, trening fizyczny przywraca zaburzoną funkcję śródbłonka w chorobach układu krążenia. Efekt ten jest widoczny w nadciśnieniu tętniczym, chorobie niedokrwiennej serca, przewlekłej niewydolności serca. Wydaje się, że poprawa rokowania zauważalna po zastosowaniu rehabilitacji kardiologicznej może być zależna od poprawy funkcji śródbłonka.
Wpływ wysiłku fizycznego w ramach rehabilitacji kardiologicznej na dysfunkcję śródbłonka – przegląd badań
Keywords: endothelial dysfunction; cardiac rehabilitation; dysfunkcja śródbłonka; rehabilitacja kardiologiczna